PENGARUH PEMBERIAN PUPUK ORGANIK CAIR URINE DOMBA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KANGKUNG (Ipomoea reptans) - Yusmaidar Sepriani (JURNAL AGROPLASMA, 2019)
This study aims to determine the effect of sheep urine manure on the kangkung cropproduction. The design is design of a randomized ( RAK) with 5 treatments, N0 (no fertilizer), N1 (30 ml urine), N2 (40 ml Urine), N3 (50ml urine) and N4 (60 ml urine).Fertilization is done 4 times, the fertilizing once every week. Each treatment was repeated 4 replications. Variable measurement is done after 28 days. The variables measured were plant height, leaf number and the production of fresh kangkung. The results showed that administration of sheep urine fermented significant against the highest plant height, number of leaves and kangkung production. The highest plant height of N4 treatment (46,86 cm) were significantly with other treatments. Achieved the highest number of leaves on the treatment T4 (9,80)). The highest kangkung production achieved in the treatment N4 (49,05 g) The conclusion of this research is that more fertilizer fermented urine provided the better performanceand best kangkung crop in the treatment T4. Keywords: sheep urine, fermented urine, Ipomoea reptans